2020
DOI: 10.1371/journal.pone.0241497
|View full text |Cite
|
Sign up to set email alerts
|

On the treatment effect heterogeneity of antidepressants in major depression: A Bayesian meta-analysis and simulation study

Abstract: Background The average treatment effect of antidepressants in major depression was found to be about 2 points on the 17-item Hamilton Depression Rating Scale, which lies below clinical relevance. Here, we searched for evidence of a relevant treatment effect heterogeneity that could justify the usage of antidepressants despite their low average treatment effect. Methods Bayesian meta-analysis of 169 randomized, controlled trials including 58,687 patients. We considered the effect sizes log variability ratio (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 21 publications
3
72
0
Order By: Relevance
“…A notable observation is that SDs were often unrelated to the proportion of treatment responders in improvement‐type models although endpoint score distributions for patients receiving simulated treatment were clearly distinguishable from those of patients receiving placebo (eg Figure 1A & C and 2A & D). The observation that comparatively simple transformations can leave standard deviations largely unaffected is in line with a recent publication arguing that meta‐analytical results of variability ratios not significantly different from 1 do not imply that there is no treatment effect heterogeneity 26 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A notable observation is that SDs were often unrelated to the proportion of treatment responders in improvement‐type models although endpoint score distributions for patients receiving simulated treatment were clearly distinguishable from those of patients receiving placebo (eg Figure 1A & C and 2A & D). The observation that comparatively simple transformations can leave standard deviations largely unaffected is in line with a recent publication arguing that meta‐analytical results of variability ratios not significantly different from 1 do not imply that there is no treatment effect heterogeneity 26 …”
Section: Discussionsupporting
confidence: 82%
“…The observation that comparatively simple transformations can leave standard deviations largely unaffected is in line with a recent publication arguing that meta-analytical results of variability ratios not significantly different from 1 do not imply that there is no treatment effect heterogeneity. 26 This study has several limitations. First, it is a simulation study considering a limited range of underlying treatment mechanisms.…”
mentioning
confidence: 92%
“…When slope estimates are closer to 0 or PLOS BIOLOGY nonlinearities are present in the mean-variance relationship, other metrics of variability such as log variability ratio (lnVR) or an approach that directly estimates the strength of association between log mean and log variance (i.e., an arm-based meta-analysis [69]) based on log SD may be more appropriate (for an example of an arm-based approach, see S9 Table and S4 Fig for galaxy plot of lnRR on lnSD). We advise that future analyses of heterogeneity pick the most appropriate statistic and model of variability based on the mean-variance relationships present in their dataset [71]. In addition to assessing the effects of treatments on variance, we further quantified differences in mean infarct volume by calculating the lnRR of the mean for each control/experimental group within a study (lnRR) and its associated sampling variance (s 2 lnRR ).…”
Section: Calculating Effect Sizesmentioning
confidence: 99%
“…Several analyses of variability based on study-level data, however, found no evidence of greater variability in the active treatment arm, and thus concluded that treatment effects are likely to be relatively constant, which suggests the scope for personalisation of treatment is limited (7)(8)(9)(10)(11)(12)(13). These findings were surprising given the widespread clinical belief that patients differ substantially in their response to medication.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of variability has recently become an area of intense interest in psychiatric research. The technique has been applied to understand variability of brain structure (1), and subsequently brain function (2)(3)(4)(5), immune function (6), and more recently to investigate variability in randomised controlled trials (RCTs) of therapeutic interventions thereby potentially providing an estimate of treatment effect heterogeneity (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%